2012
DOI: 10.1007/s10725-012-9676-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of BABY BOOM and LEAFY COTYLEDON genes in sweet pepper (Capsicum annuum L.) genome by their partial gene sequences

Abstract: Haploid plant production via anther culture is a valuable tool to rapidly create pure lines for plant breeding programs. Some sweet pepper (Capsicum annuum L.) varieties produce embryogenic anther culture readily, while others do not respond at all. The switching of microspore developmental program from gametophyte-to sporophytetype is regulated by transcription factors like BABY BOOM (BBM) and LEAFY COTYLEDON (LEC). Genes encoding these transcription factors have not been found in sweet pepper yet. The sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 40 publications
(48 reference statements)
1
17
0
Order By: Relevance
“…Several members in the AP2/ERF family had also been reported to be involved in microspore-, somatic- and zygotic embryogenesis 32 . In this study, the radish orthologs of APETALA2 ( AP2 , negatively controlling cell proliferation during seed development), AINTEGUMENTA ( ANT , expressing in the primordia of cotyledons) and BABY BOOM ( BBM , promoting cell proliferation and morphogenesis during embryogenesis) were differentially expressed during radish embryogenesis and seed development, consistent with their actions in Arabidopsis thaliana 17 , Brassica napus 16 , Capsicum annuum 37 and Elaeisguineensis 38 . These findings suggested that these TFs potentially participate in the specific process embryogenesis and early seedling development in radish 9 .…”
Section: Discussionsupporting
confidence: 71%
“…Several members in the AP2/ERF family had also been reported to be involved in microspore-, somatic- and zygotic embryogenesis 32 . In this study, the radish orthologs of APETALA2 ( AP2 , negatively controlling cell proliferation during seed development), AINTEGUMENTA ( ANT , expressing in the primordia of cotyledons) and BABY BOOM ( BBM , promoting cell proliferation and morphogenesis during embryogenesis) were differentially expressed during radish embryogenesis and seed development, consistent with their actions in Arabidopsis thaliana 17 , Brassica napus 16 , Capsicum annuum 37 and Elaeisguineensis 38 . These findings suggested that these TFs potentially participate in the specific process embryogenesis and early seedling development in radish 9 .…”
Section: Discussionsupporting
confidence: 71%
“…Another key regulator of plant cell totipotency is BBM . BBM can induce embryogenesis in differentiated cells and could be a vital factor in plant embryogenesis development (Irikova et al, 2012). BBM triggers a set of genes like LEC1 and LEC2 , as well as ABI3 and the FUS3 network, which together activate SE (Horstman et al, 2017).…”
Section: Transcription Factors and Signal Transduction Involved In Somentioning
confidence: 99%
“…BABY BOOM (BBM) was originally isolated from Brassica embryogenic microspore cultures; when ectopically expressed in Arabidopsis , induced spontaneous SE [ 100 ]. Although BBM was proven to be capable of inducing SE in numerous plant species [ 57 , 101 , 102 ], only few authors focus on BBM utility as a suitable marker to monitor SE progress [ 60 , 103 ]. Our results confirmed transcriptional induction of MtBBM only in callus of the embryogenic M9-10a line, which is consistent with results from Theobroma cacao SE where expression of TcBBM was significantly higher in undifferentiated embryogenic callus, compared to non-embryogenic callus.…”
Section: Discussionmentioning
confidence: 99%